Fertilizer phosphorus in various fractions of soil phosphorus - Kaila, Armi (Agricultural and Food Science, 1963)
In the present work an attempt was made to follow in laboratory experiments the distribution of fertilizer phosphorus into the various fractions of soil inorganic phosphorus using the procedure of CHANG and JACKSON (3). Four mineral soils were selected for these studies. Their acidity varied from pH 3.7 to pH 6.0 (in 0.02 N CaCl2), clay content from 28 to 54 per cent, and the indicator of their capacity to sorb phosphate from 135 to 1000. The fertilizers studied were superphosphate, CaHPO4∙2H20 (chemical grade), hyperphosphate, basic slag, and a preparate of fused apatite called in this work the »Finnish phosphate». In the soil samples incubated with an application of fertilizers corresponding to about 500 ppm P for 24 weeks at room temperature, the fertilizer phosphorus accumulated in various fractions mainly according to the properties of the soils. In the two acid Litorina soils rich in sesquioxides and with a high capacity to sorb phosphate, the main part of the fertilizer phosphorus was found in the alkali-soluble fraction in most the cases, with a not insignificant amount in the fluoride-soluble fraction. The only exceptions occurred in the distribution of hyperphosphate phosphorus, and to a lesser degree, of phosphorus in basic slag, in the sample particularly rich in iron where a large portion of fertilizer phosphorus remained in the acid-soluble forms. In the slightly acid sandy clay the distribution of the fertilizer phosphorus into the different fractions was more uniform than in the other soils, only the hyperphosphate phosphorus largely remained in the acid-soluble forms. In the acid silt soil with a typical average capacity to sorb phosphate, the main part of the fertilizer phosphorus was in all cases found in the fluoride-soluble fraction. The equal distribution of superphosphate phosphorus and dicalcium phosphate phosphorus in the respective incubated soils is in accordance with the claim that monocalcium phosphate rapidly turns over into dicalcium phosphate in the soil. The well known slow mobilization of hyperphosphate phosphorus in all but the very acid soils is also demonstrated by the present results, but the slow reaction of this fertilizer in the acid soil with a very high content of iron may be worth of further studies. The compounds of basic slag seem to be mobilized fairly rapidly even in the less acid soils. The results concerning the »Finnish phosphate» indicate that this preparate may be a valuable phosphorus fertilizer in various kinds of our soils. During the fractionation procedure the reactions of the fertilizer phosphorus compounds with the soil constituents seem to be marked, the trend and the rate of the reactions largely depending on the properties of the soils.